One-Pot Access to Diverse Functionalized Pyran Annulated Heterocyclic Systems Using SCMNPs@BPy-SO3H as a Novel Magnetic Nanocatalyst - Ke Chen; Guangzu He; Qiong Tang; Qahtan A. Yousif (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
The SCMNPs@BPy-SO3H catalyst was prepared and characterized using Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA), Vibrating Sample Magnetometry (VSM), Energy Dispersive X-ray Spectroscopy (EDX), X-ray Diffraction (XRD), and Scanning Electron Microscopy (SEM). Afterwards, its capability was efficiently used to promote the one-pot, three-component synthesis of pyrano[2,3-c]pyrazole and 2-amino-3-cyano-pyrano[3,2-c]chromen-5(4H)-one derivatives. The strategy resulted in the desired products with excellent yields and short reaction times. The SCMNPs@BPy-SO3H catalyst was readily recovered using a permanent magnetic field and it was reused in six runs with a slight decrease in catalytic activity. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).